Tinnitus pitch, masking, and the effectiveness of hearing aids for tinnitus therapy. - McNeill, Celene; Távora-Vieira, Dayse; Alnafjan, Fadwa; Searchfield, Grant D.; Welch, David (International Journal of Audiology, 2012)
Objective: To assess the benefits of hearing aids on tinnitus according to the tinnitus reaction questionnaire (TRQ; Wilson et al, 1991), to verify whether the degree of masking provided by the hearing aid influenced the TRQ score, to examine whether the matched tinnitus pitch predicted the effectiveness of hearing aids in masking tinnitus, and to determine whether prescription of high-frequency amplification might be desirable in tinnitus management when tinnitus pitch is high. Design and study sample: A retrospective evaluation of the clinical outcomes of 70 tinnitus patients fitted with hearing aids was undertaken. The primary outcome measure was the TRQ, with a secondary subjective measure of tinnitus masking. Results: Participants who achieved masking with their hearing aids had greater reduction in TRQ scores. Masking was more likely to be achieved when participants had good low-frequency hearing and tinnitus pitch fell into the frequency range of the hearing aids. Conclusions: The results support the use of hearing aids for tinnitus management, and suggest that masking may be a significant contributor to hearing aid success, implying that high-frequency amplification may be effective in high-pitch tinnitus.